'Enough is enough': a mixed methods study on the key factors driving UK NHS nurses' decision to strike - Daniel Sanfey (BMC, 2024)
Abstract Background The UK National Health Service (NHS) is one of the largest employers in the world and employs around 360,000 registered nurses. Following a protracted pay dispute in December 2022 NHS nurses engaged in industrial action resulting in the largest nurse strikes in the 74-year history of the NHS. Initially it appeared these strikes were a direct consequence of pay disputes but evidence suggests that the situation was more complex. This study aimed to explore what the key factors were in driving UK NHS nurses' decision to strike. Methods A convergent parallel mixed methods design was used. The study was conducted throughout the UK and involved participants who were nurses working for the NHS who voted in favour of strike action. Data collection involved the use of an online survey completed by 468 nurses and 13 semi-structured interviews. Descriptive and inferential statistics were used for quantitative data analysis and a process of inductive thematic analysis for the qualitative data. The quantitative and qualitative data were analysed separately and then integrated to generate mixed methods inferences. Results The quantitative findings showed that patient safety, followed by staff shortages, pay, and unmanageable work demands were the most important factors encouraging nurses' decision to strike. The qualitative findings served to further the understanding of these factors particularly in relation to participants' perception of the NHS and the consequences of inadequate pay and staff shortages. Three overarching and overlapping themes represented the qualitative findings: Save our NHS, Money talks, and It's untenable. Integration of the findings showed a high level of concordance between the two data sets and suggest that the factors involved are interconnected and inextricably linked. Conclusions The UK NHS is a challenging and demanding work environment in which the well-being of its patients is dependent on the well-being of those who care for them. Concerns relating to patient welfare, the nursing profession and the NHS played a large part in driving UK NHS nurses' decision to strike. In order to address these concerns a focus on recruitment and retention of nurses in the NHS is needed.